Dietary recommendations in Spain –affordability and environmental sustainability?. (1st May 2020) - González-García, Sara; Green, Rosemary F.; Scheelbeek, Pauline F.; Harris, Francesca; Dangour, Alan D.
Abstract: Global food demand is increasing due to population growth and dietary transitions, resulting from rising incomes, are associated with increased prevalence of non-communicable diseases. Improving the sustainability of the food sector is also critical for achieving the Sustainable Development Goals. This study assesses for the first time the greenhouse gases emissions (Carbon Footprint – CF), the water footprint (WF) and the cost of three omnivorous diets recommended in Spain due to their health benefits: the Mediterranean diet (MD), the Southern European Atlantic diet (SEAD) and the Spanish dietary guidelines (NAOS). Analysis was conducted using standard Life Cycle Assessment and WF methods together with current Spanish food price data. The dietary energy recommendation of the SEAD is greater than that of MD and NAOS (11 and 15% respectively), and SEAD also has greater animal source food content than the other two diets. SEAD has a concomitantly higher CF, WF and cost scores in comparison with MD (+30%,  +23% and +21% respectively) and NAOS (+15%,  +9% and +21% respectively). Adjusting recommendations to meet the suggested Spanish adult dietary energy of 2228 kcal∙capita −1 ∙day −1 changed the environmental profiles of the diets and the NAOS has the highest environmental impact. However, the isocaloric diets had approximately the same cost. Analysis of the WF of the diets identified the major contribution of precipitation (the green WF) to the overall WF (88% of the total) and the significant contribution of animal-source foods to dietary WF. Regardless of the dietary scenario, better scores were identified for the Spanish recommendations analysed than those reported for other healthy diets identified in Europe. Differences in the recommended intake levels of certain food groups, cooking techniques and the origin of food products are behind these results. Environmental indicators should be considered alongside nutrition and health metrics when defining national dietary guidelines. Supporting citizens to follow healthy and environmentally-friendly dietary recommendations through, among other things, information campaigns and nutritional education programmes is essential. It is recommended the incorporation not only of health, but also of environmental indicators of these dietary options in the national dietary guidelines, as well as implementation of information campaigns and nutritional education programs among citizens to promote their adhesion since balanced dietary habits rich on plant-based products and low on animal-based ones involve multiple health and environmental benefits. Graphical abstract: Image 1 Highlights: Three omnivorous and balanced diets supported by Spanish Health agencies are compared. The energy inputs are different being higher for the diet richer in animal products. This diet reports larger carbon and water footprints as well as costs. Adjusting diets to the same dietary energy results in totally opposite results. Conclusions are sensitive to assumptions and data quality considered in the analysis